1998
DOI: 10.1161/01.res.82.7.810
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Anion From the Adventitia of the Rat Thoracic Aorta Inactivates Nitric Oxide

Abstract: Abstract-The purpose of this study was to determine whether superoxide anion is produced endogenously in the rat aortic adventitia and whether sufficient superoxide anion is produced to interfere with the response of the rat aorta to nitric oxide. Relaxation was measured in rings of the rat thoracic aorta, which were oriented so that the adventitial or luminal surface could be preferentially exposed to nitric oxide or sodium nitroprusside. To accomplish this, the rings were mounted (1) with the adventitia faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
194
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(212 citation statements)
references
References 51 publications
16
194
1
1
Order By: Relevance
“…The details of this assay have been published previously (Wang et al, 1998). Brie¯y, aortae were cut into transverse rings 10 mm in length.…”
Section: Quantification Of Superoxide Anion By Measurement Of the Amomentioning
confidence: 99%
“…The details of this assay have been published previously (Wang et al, 1998). Brie¯y, aortae were cut into transverse rings 10 mm in length.…”
Section: Quantification Of Superoxide Anion By Measurement Of the Amomentioning
confidence: 99%
“…1 This enzyme complex plays a major role in superoxide ion production in blood vessels. [1][2][3][4] Superoxide ions are known to avidly interact with nitric oxide (NO), reducing its bioactivity by generating peroxynitrite. [2][3][4] Increased activity of the NAD(P)H oxidase system is expected to be associated with reduced NO levels, vascular dysfunction, hypertension and salt sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Superoxide ions are known to avidly interact with nitric oxide (NO), reducing its bioactivity by generating peroxynitrite. [2][3][4] Increased activity of the NAD(P)H oxidase system is expected to be associated with reduced NO levels, vascular dysfunction, hypertension and salt sensitivity. [4][5][6] The latter, is known to be associated with reduced NO bioactivity [7][8][9][10][11][12][13] and increased superoxide production.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recent in vivo and in vitro studies have implicated the adventitial fibroblast as a major site for superoxide production in response to angiotensin II administration, 12,13 and we have recently shown that adventitial fibroblasts are a major source of the inducible form of NO synthase in aortic tissue after the in vivo administration of endotoxin to produce an inflammatory response. 14 To begin to evaluate the possible role of NO in modulating vascular remodeling during hypertension, we have used procedures for obtaining adult rat adventitial fibroblasts in culture and have studied the effects of NO on cell proliferation under standardized conditions in which quiescent cells were stimulated with FCS.…”
mentioning
confidence: 99%